Availability of the HPV Vaccine in Regional Pharmacies and Provider Perceptions Regarding HPV Vaccination in the Pharmacy Setting - Jill M. Maples; Nikki B. Zite; Oluwafemifola Oyedeji; Shauntá M. Chamberlin; Alicia M. Mastronardi; Samantha Gregory; Justin D. Gatwood; Kenneth C. Hohmeier; Mary E. Booker; Jamie D. Perry; Heather K. Moss; Larry C. Kilgore (Vaccines, 2022)
There is increasing support for HPV vaccination in the pharmacy setting, but the availability of the HPV vaccine is not well known. Additionally, little is known about perceptions of medical providers regarding referring patients to community pharmacies for HPV vaccination. The purpose of this study was to determine HPV vaccine availability in community pharmacies and to understand, among family medicine and obstetrics–gynecology providers, the willingness of and perceived barriers to referring patients for HPV vaccination in a pharmacy setting. HPV vaccine availability data were collected from pharmacies in a southern region of the United States. Family medicine and obstetrics–gynecology providers were surveyed regarding vaccine referral practices and perceived barriers to HPV vaccination in a community pharmacy. Results indicated the HPV vaccine was available in most pharmacies. Providers were willing to refer patients to a community pharmacy for HPV vaccination, despite this not being a common practice, likely due to numerous barriers reported. Pharmacist-administered HPV vaccination continues to be a commonly reported strategy for increasing HPV vaccination coverage. However, coordinated efforts to increase collaboration among vaccinators in different settings and to overcome systematic and legislative barriers to increasing HPV vaccination rates are still needed.